'Academic Mobility for Development' as A Contested Notion: An Analysis of the Reach of the Chinese State in Regulating the Transnational Brains. (December 2014) - Leung, Maggi W.H.
Abstract This paper gauges the reach of the state in regulating the flows of academics and harnessing them for development in China. Drawing upon a review of policy documents, secondary data and fieldwork findings from a research project that studies the developmental impact of academic mobility among Chinese scholars active in the Chinese‐German academic space, this paper challenges the 'talents sans frontières' notion on the one hand, and illustrates the limits of the state on the other. Mobile scholars are conceptualised as active agents who are nested in, and hence being regulated by and at the same time shaping the Chinese state and its policies. Mobile scholars (and their local(ised) colleagues) are engaged in multiple relationships (ranging from collaborative, contradictory to conflictual ones) with the state, sometimes reinforcing and at other times toppling its notions of development. These relationalities call for new interpretations of the dynamic, contextualised and complex mobility‐development nexus.